Sectarian Translation of the Qur’an in Indonesia: The Case of the Ahmadiyya - Ahmad Najib Burhani (Al-Jami'ah Research Centre, 2015)
Ahmadiyya’s translations of the Quran have some distinctive characteristics compared to the translations from Sunni Muslims. However, these translations, particularly Soedowo-Dutch translation of Muhammad Ali’s The Holy Quran, have been influential in Indonesian Sunni community in the first half of the 20th century. Against the opposition from the Muhammadiyah and the fatwa from Muhammad Rashid Rida of Egypt, which prohibited the use of Ahmadiyya’s translation, the Soedewo-Dutch translation was widely used by Dutch-educated intelligentsia as a main source to know about Islam. This article specifically answers the following questions: Why did Ahmadiyya’s translations of the Quran have a significant place in Indonesia? What was the appeal of these translations to Indonesian intelligentsia? What is the contribution of these translations to the study of the Quran in this country? This paper argues that the success of Ahmadiyya’s translation, particularly the Dutch version, during the revolution era is based on three reasons: language (Dutch is the language of intelligentsia), content (which fit with the need of intelligentsia who seek a harmonious understanding between religie and wetenschap), and form (the only available rendering of the Quran in modern form of publication). In the context of ideology, the reception of Muslim intelligentsia was mainly for their contribution in defending Islam against the penetration of Christian mission and the coming of anti-religion ideologies, particularly materialism and atheism, by strongly challenging their doctrines. [Terjemah al-Quran versi Ahmadiyah memiliki beberapa karakteristik yang berbeda jika dibandingkan dengan terjemah versi Islam sunni pada umumnya. Namun demikian, terjemah seperti di atas, khususnya terjemah al-Quran dalam bahasa Belanda –yang dialih-bahasakan dari The Holy Qur’ān karya Muhammad Ali oleh Soedowo– cukup berpengaruh di masyarakat muslim Indonesia pada paruh pertama abad ke-20. Bertentagan dengan fatwa dari Muhammadiyah maupun dari Muhammad Rashid Rida yang melarang penggunaan terjemah versi Ahmadiyyah, terjemha Soedewo ini justru menjadi rujukan bagi kalangan terdidik untuk memahami Islam. Tulisan ini secara khusus menjawab pertanyaan: mengapa terjemah al-Quran versi Ahmadiyyah ini cukup berpengaruh di Indonesia, apa yang menarik dari tterjemah ini bagi mereka, serta apa sumbangan pemikiran terjemah ini pada perkembangan keilmuan al-Quran di negeri ini. Menurut penulis, terjemah versi Ahmadiyyah, khususnya yang berbahasa Belanda, mengalami kesuksesan pada masa revolusi dipengaruhi oleh tiga hal: (1) bahasa Belanda yyang dipakai adalah bahasa kalangan terdidik, (2) isinya sesuai dengan kebutuhan kalangan terpelajar yang ingin mencari pemahaman yang harmonis antara agama dan ilmu pengetahuan, dan (3) terjemah ini merupakan satu-satunya bentuk publikasi modern dari terjemah al-Quran yang ada pada masa itu. Dalam konteks ideologi, penerimaan kaum intelektual ini terutama terkait dengan upaya perlawanan Islam terhadap tekanan misi Kristen dan masuknya ideologi-ideologi anti agama, khususnya materialisme dan atheisme.]